(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Educational games can be used to teach several behavioral repertoires, which shows the relevance of their development and evaluation. This study aimed to assess whether playing an adapted version of Resgarte increases the probability of interconnection of repertoires during problem-solving. Thirty-six undergraduate students participated in the study. An intra-group experimental design with pre- and post-intervention evaluation was carried out, with the game as an independent variable. Participants were submitted to problem-solving tests before and after the intervention. Test sessions were video recorded, and five judges evaluated the effectiveness of their problem resolutions. Most participants (60,60%) showed an increased number of problems solved after the intervention and started to present more interconnection of repertoires in problem-solving (75,75%). We concluded that the interconnection of repertoires could be taught through contingency arrangements in a game.